Direct closed diaphragm injuries: diagnosis and treatment - E. S. Vladimirova; I. V. Ermolova; F. A. Chernousov; V. G. Kotandzhan; E. B. Nikolaeva; I. E. Popova; O. A. Alekseechkina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Background. Diaphragmatic injuries caused by ribs or direct blunt diaphragmatic injuries at various periods after trauma are associated with the development of hemothorax, pneumohemothorax, and pulmonary contusion, which lead to secondary pulmonary complications. Issues of diagnosis and management of direct diaphragmatic injuries remain largely unresolved. Objective: to evaluate the capabilities of radiological diagnostic methods and determine treatment approaches for direct blunt diaphragmatic injuries. Object and methods. The study included 66 patients with combined and isolated chest trauma, rib fractures, and direct blunt diaphragmatic injuries requiring pleural drainage and other surgical treatment methods (video-assisted thoracoscopy, video laparoscopy, laparotomy, thoracotomy). Patient age ranged from 16 to 84 years, with 54 men and 12 women. The sample was formed over the period from January 1983 to December 2024 from patients treated at the N.V. Sklifosovsky Research Institute of Emergency Medicine. Results. Diagnosing direct blunt diaphragmatic injuries using radiological diagnostic methods is quite challenging, as direct signs require proof of abdominal organ displacement through the diaphragmatic defect. Diagnostic difficulties of direct blunt diaphragmatic injuries are due to small penetrating diaphragmatic defects or absence of penetrating defects in incomplete injuries. The leading role in detecting direct blunt diaphragmatic injuries belongs to methods that allow visual assessment of diaphragmatic condition (video-assisted thoracoscopy, video laparoscopy, laparotomy, thoracotomy, autopsy). Conclusions. Extended use of video-assisted thoracoscopy in blunt chest trauma reveals direct blunt diaphragmatic injuries in early stages and allows avoidance of late complications.